The Effect of Adding Lactic Acid Bacteria Type Pediococcus pentosaceus on Phosphorus Content of Rice Bran - Al Gifari, Zaid; Andriati, Rina; Ali, Muhamad; anwar, Khairil (Faculty of Animal Husbandry, University of Mataram, 2025)
This study aims to evaluate the effect of fermentation with lactic acid bacteria Pediococcus pentosaceus on phosphorus content in rice bran. This bacteria is a probiotic isolated from animal intestinal microflora, with high colonization ability due to its suitability to the original environment. The study focused on the ability of the isolate to break down phytic acid bound to the bran, with the main indicator being an increase in phosphorus levels. The fermentation results showed the highest viability at an incubation temperature of 37°C, with a maximum number of 240 × 10⁸ CFU/g at 12 hours, but decreased thereafter. Although there was an increase in phosphorus levels, the results were not statistically significant (p>0.05) in both dry bran (P1) and wet bran (P2) treatments. The highest increase in phosphorus occurred at a temperature of 44°C (0.91±0.004%; +25%) and at 37°C (0.87±0.002%; +19%). This suggests that temperature affects the effectiveness of fermentation, but water content and incubation time may be limiting factors. Overall, fermentation of rice bran with P. pentosaceus did not show a significant increase in phosphorus levels.